ANALYSIS LANGUAGE ENVIRONTMENT OF ENGLISH DEPARTMENT AT MADURA UNIVERSITY IN ENGLISH LANGUAGE LEARNING - Sholeh, Darus; Yunanto, Fredy (The Ellite of Unira, 2025)
The aim of this research to describe the naturalness of environment on English speaking skills at English study program Madura University. This research is qualitative research by using narrative. Researched obtained data from, observation, interview and documentation. The research informants were the sixth semester of English Study Program at Madura University academic 2021/2022.Based on the result of the study show the students in the English study program feel in the English study program feel insecure when speaking in public, mix English and Indonesian when the student don’t know the vocabulary. The English study program does not have a language laboratory facility that helps students to develop their abilities, the students often communicate with their classmates and with teacher, but when talking to the lecturer most are afraid of being wrong. Students only talk in class and during class. When, outside class rarely to speak English.